2020
DOI: 10.3389/fgene.2020.00092
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Runs of Homozygosity Revealed Selection Signatures in Bos indicus

Abstract: Genome-wide runs of homozygosity (ROH) are suitable for understanding population history, calculating genomic inbreeding, deciphering genetic architecture of complex traits and diseases as well as identifying genes linked with agro-economic traits. Autozygosity and ROH islands, genomic regions with elevated ROH frequencies, were characterized in 112 animals of seven Indian native cattle breeds (B. indicus) using BovineHD BeadChip. In total, 4138 ROH were detected. The average number of ROH per animal was maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 33 publications
(54 reference statements)
9
54
0
1
Order By: Relevance
“…Altogether, MDS, AMOVA, PCA and MJ network analyses demonstrated that geographical distribution is not a reliable predictor of paternal variation, and Y-lineages appear to be more related to function of the Indian cattle breeds. The clustering of Indian cattle breeds based on genome-wide runs of homozygosity further supports the view 38 .…”
Section: Discussion Finding New Haplotypes In Indicine Cattlesupporting
confidence: 66%
“…Altogether, MDS, AMOVA, PCA and MJ network analyses demonstrated that geographical distribution is not a reliable predictor of paternal variation, and Y-lineages appear to be more related to function of the Indian cattle breeds. The clustering of Indian cattle breeds based on genome-wide runs of homozygosity further supports the view 38 .…”
Section: Discussion Finding New Haplotypes In Indicine Cattlesupporting
confidence: 66%
“…ROH analyses were performed separately for each population, using SVS software. No linkage disequilibrium (LD)-based pruning was performed and, as in [ 17 ], the minimum ROH length was set to 1 Mb to avoid the detection of short and common ROH across the genome due to LD. The ROH were defined setting a minimum of 1000 Kb in length and 60 homozygous consecutive SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…2019; Dixit et al . 2020). Crossbreeding with taurine dairy breeds enhances dairy production (Wakchaure et al .…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%